High-performance thermal transfer ribbon for laser thermal transfer printing as well as preparation method and application of high-performance thermal transfer ribbon

By using a photothermal conversion layer composed of carbon nanotubes and graphene in laser thermal transfer technology, combining high-performance substrates and dyes or ink layers, the efficiency and quality problems of existing carbon tapes in laser thermal transfer are solved, and the transfer effect of high-efficiency, high-definition, and multi-material adaptation is achieved.

CN119953095APending Publication Date: 2025-05-09HUNAN DINGYIYUAN TECH DEV CO LTD +1
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202510155576.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-12
Publication Date
2025-05-09

AI Technical Summary

Technical Problem

In the laser thermal transfer technology, the existing carbon tape has problems such as low transfer efficiency, poor pattern quality and limited adaptability to the substrate.

Method used

The photothermal conversion layer consisting of carbon nanotubes, graphene and acrylic resin binder is used to combine transparent film substrates and high-performance thermal sublimation dyes or ink layers to improve the overall performance of the carbon tape by optimizing the coating process and hierarchy structure.

Benefits of technology

It achieves efficient and high-quality transfer effect, improves the transfer efficiency by 30%-50%, pattern clarity by 20%-30%, color saturation by 15%-25%, and enhances the adhesion and friction resistance to different substrates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119953095A_ABST
    Figure CN119953095A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of laser heat transfer printing, and particularly relates to a high-performance thermal transfer ribbon for laser heat transfer printing and a preparation method and application of the high-performance thermal transfer ribbon. The high-performance thermal transfer ribbon for laser thermal transfer printing comprises an ink layer, a photothermal conversion layer, a demolding layer and a base material which are arranged in sequence, or the thermal sublimation dye layer, the photothermal conversion layer and the base material are sequentially arranged. The high-performance thermal transfer ribbon provided by the invention can be applied to laser thermal transfer printing, can realize an efficient and high-quality transfer printing effect, and has high adaptability to different printing stocks.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of laser thermal transfer, and in particular relates to a high-performance carbon ribbon for laser thermal transfer and a preparation method and application thereof. Background Art

[0002] Laser thermal transfer is a printing technology that uses laser energy to make a specific layer on the carbon ribbon absorb heat, causing physical or chemical changes, thereby transferring ink or dye to the substrate to form a pattern. Laser thermal transfer technology has been widely used in many fields due to its advantages such as high precision and non-contact printing.

[0003] In commercial printing (such as label and ticket printing), existing carbon ribbons may meet the needs of high-speed printing, but the printed patterns are prone to wear and fade. In personalized customized printing (such as customized gifts and decorative painting printing), it is difficult to achieve high color accuracy and rich color gradation printing effects. In industrial logo printing, the adhesion and corrosion resistance to substrates of different materials are insufficient.

[0004] At present, the main methods to improve the performance of carbon ribbon are:

[0005] 1. Improve the ink formula to improve the color development and transferability of the ink, but this may lead to decreased ink stability or increased costs.

[0006] 2. Optimize the ribbon substrate, such as choosing a stronger or smoother material, but the compatibility of the substrate with other layers may be affected.

[0007] 3. Adjust the coating process, such as changing the coating thickness or method, but the process complexity and cost will also increase accordingly.

[0008] However, the above methods all have their own disadvantages:

[0009] 1. When improving the ink formula, the new ingredients may react chemically with other layers, affecting the overall performance of the ribbon; while improving the color rendering, the stability of the ink in different environments may be reduced; the increase in cost reduces the market competitiveness of the product.

[0010] 2. Optimizing the substrate may not be able to simultaneously take into account good bonding with each coating and meet different printing requirements (such as flexibility and wear resistance); changes in substrate performance may require adjustments to the entire production process, increasing production costs and technical difficulties.

[0011] 3. Adjusting the coating process requires precise control of multiple parameters, and high requirements for equipment and process; changes in coating thickness or method may cause coating uniformity problems and affect transfer quality.

[0012] Generally speaking, in traditional thermal transfer technology, common carbon ribbons have problems such as low transfer efficiency, poor pattern quality (such as low clarity, insufficient color saturation), and limited adaptability to substrates. Therefore, it is difficult to apply to laser thermal transfer technology. Summary of the invention

[0013] In order to solve the deficiencies of the prior art, the present invention provides a high-performance carbon ribbon for laser thermal transfer and a preparation method and application thereof. The high-performance carbon ribbon provided by the present invention can be applied to laser thermal transfer, can achieve efficient and high-quality transfer effects, and has high adaptability to different substrates.

[0014] The technical solution provided by the present invention is as follows:

[0015] A high-performance carbon ribbon for laser thermal transfer includes an ink layer, a light-to-heat conversion layer, a demoulding layer and a substrate which are arranged in sequence. The high-performance carbon ribbon for laser thermal transfer can be used as a full transfer carbon ribbon.

[0016] A high-performance carbon ribbon for laser thermal transfer includes a thermal sublimation dye layer, a light-to-heat conversion layer and a substrate which are arranged in sequence. The high-performance carbon ribbon for laser thermal transfer can be used as a thermal sublimation carbon ribbon.

[0017] The high-performance carbon ribbon for laser thermal transfer provided by the above technical solution can be applied to laser thermal transfer, can achieve efficient and high-quality transfer effects, and is suitable for a variety of different substrates.

[0018] Substrate

[0019] Materials and function realization: A transparent film with a thickness of 6-12μm is selected as the substrate because it has good mechanical strength, chemical stability, dimensional stability and flexibility. For example, PET film has a high surface flatness, which is conducive to the uniform coating of each coating. Its performance changes little under different temperature and humidity environments, which can ensure the stability of the carbon ribbon under various use conditions. The transparent film can be selected from polyethylene terephthalate film (PET), polypropylene film, polyethylene naphthalate film, polyethylene film, polyvinyl alcohol film or polymethyl methacrylate film.

[0020] Surface treatment method: The surface of the substrate is treated with corona to make the surface dyne value reach 42-50, which enhances its adhesion with the light-heat conversion layer. The corona treatment time is 5-10 seconds, the power is 1-3kW, and the next coating operation is carried out immediately after the treatment to prevent surface contamination from affecting adhesion.

[0021] Light-to-heat conversion layer

[0022] Material composition and function realization: It is composed of carbon nanotubes (mass fraction 8%-15%), graphene (mass fraction 3%-8%) and acrylic resin binder (mass fraction 77%-89%). Carbon nanotubes and graphene have excellent light absorption properties, can efficiently absorb laser energy and quickly convert it into heat energy, and provide heat for the sublimation or melting of the thermal sublimation dye layer or ink layer. The acrylic resin binder ensures the firm bonding between the photothermal conversion layer and the PET substrate and the thermal sublimation dye layer / ink layer, and has good flexibility and heat resistance. The photothermal conversion layer is black as a whole, which further improves the photothermal efficiency. At the same time, carbon nanotubes and graphene have good adhesion to the acrylic resin binder respectively.

[0023] Preparation and coating process: Add carbon nanotubes and graphene to an organic solvent (such as N-methylpyrrolidone) containing an appropriate amount of dispersant (such as polyvinyl pyrrolidone, with a mass fraction of 5%-10% of the total mass of carbon nanotubes and graphene), and ultrasonically disperse for 40-60 minutes to form a uniform dispersion. Then dissolve the acrylic resin binder in the above dispersion and stir for 60-90 minutes to obtain a light-to-heat conversion layer coating. Use a gravure coater for coating, the coating speed is 100-200m / min, the drying temperature is 70-90℃, and the coating thickness is controlled at 0.3-0.8μm.

[0024] Sublimation dye layer or ink layer

[0025] If it is a thermal sublimation dye layer, a high-performance thermal sublimation dye with a sublimation temperature of 100-200°C is selected, such as commercially available azo and anthraquinone dyes, which have the characteristics of bright colors, high color fastness, small particle size (0.05-0.3μm) and uniform distribution, and can achieve high-resolution and high-color saturation printing effects. The resin binder is one of cellulose, polyurethane resin, and polyvinyl butyral resin. The ratio of resin to dye is 1:1 to 1:2.

[0026] If it is an ink layer, the ink formula is composed of thermoplastic polyurethane resin (mass fraction 30%-45%), pigment (such as carbon black, organic pigment, mass fraction 15%-25%), wax additive (such as polyethylene wax, mass fraction 10%-20%) and organic solvent (such as butanone, toluene, mass fraction 20%-30%). Thermoplastic polyurethane resin provides good adhesion and flexibility, pigment ensures color presentation, wax additive adjusts the melting point and fluidity of the ink, and organic solvent facilitates the coating and drying of the ink.

[0027] Thermoplastic polyurethane resin may be replaced by polyester resin or polyamide resin.

[0028] Additives and function optimization:

[0029] A small amount of antioxidant (such as hindered phenol antioxidant, mass fraction of 1%-3% of the dye mass) can be added to the thermal sublimation dye layer to prevent the dye from oxidative decomposition during high-temperature transfer, and also to prevent the decomposition of the dye during long-term storage, thereby improving the stability and service life of the dye.

[0030] A dispersant (such as a high molecular weight polymer dispersant, with a mass fraction of 3%-6% of the pigment mass) is added to the ink layer to ensure uniform dispersion of the pigment, and a leveling agent (such as a silicone leveling agent, with a mass fraction of 0.5%-1.5% of the total ink mass) is added to improve the surface flatness of the ink layer.

[0031] Coating parameters and thickness control:

[0032] The thermal sublimation dye layer is coated by gravure coating, with a coating speed of 100-200m / min, a drying temperature of 70-90°C, and a thickness controlled at 0.5-1.5μm according to color requirements (such as 0.8-1.2μm for cyan, 0.6-1.0μm for magenta, and 0.5-0.8μm for yellow).

[0033] The ink layer is applied by gravure coating at a coating speed of 100-200 m / min, a drying temperature of 60-80°C, and a thickness of 0.5-3 μm.

[0034] Release layer

[0035] The release layer is provided when the color supplied is an ink layer.

[0036] Materials and functions: It is composed of polytetrafluoroethylene powder (mass fraction 5%-10%), silicon dioxide nanoparticles (mass fraction 3%-6%) and polyester resin (mass fraction 84%-92%). Polytetrafluoroethylene powder provides excellent demoulding performance, reduces the peeling force of the carbon ribbon during the transfer process, and prevents ink or dye residue; silicon dioxide nanoparticles enhance the hardness and wear resistance of the demoulding layer, while improving its surface roughness, which is conducive to the transfer of ink or dye; polyester resin acts as a binder to ensure good bonding between the demoulding layer and the ink layer.

[0037] PTFE powder can be replaced by other materials with low friction coefficient, such as boron nitride.

[0038] The silica nanoparticles can be replaced by different types of fillers, such as calcium carbonate nanoparticles.

[0039] Preparation and coating process: Add polytetrafluoroethylene powder and silicon dioxide nanoparticles to polyester resin solution (polyester resin is dissolved in a mixed solvent of toluene and butanone, with a mass ratio of 1:1-2:1), use a high-speed stirrer to stir at 1500-2500rpm for 30-60 minutes to prepare a release layer coating. Use a gravure coater for coating, the coating speed is 100-200m / min, the drying temperature is 60-80℃, and the thickness is controlled at 0.1-0.3μm.

[0040] When used as a full transfer carbon ribbon, the preparation method provided by the present invention comprises the following steps: preparing a substrate, a release layer, a light-to-heat conversion layer and an ink layer in sequence.

[0041] When used as a thermal sublimation carbon ribbon, the preparation method provided by the present invention comprises the following steps: preparing a substrate, a light-to-heat conversion layer and a thermal sublimation dye layer in sequence.

[0042] The present invention also provides the application of high-performance carbon ribbon for laser thermal transfer, which can use ultraviolet light, visible light or infrared light as the laser source. The laser thermal transfer can directly use the existing laser thermal transfer.

[0043] In the present invention:

[0044] The reasonable combination of light-to-heat conversion layer, release layer and protective layer synergistically improves the comprehensive performance of the carbon ribbon.

[0045] The selection of materials for each layer, such as the combination of carbon nanotubes and graphene in the light-to-heat conversion layer, the high-performance ingredients in the ink layer or dye layer, the special additives in the release layer, and the design of the combination of the protective layer and the release layer, ensures efficient and high-quality transfer effects of laser thermal transfer, as well as high adaptability to different substrates.

[0046] The coating process and parameter control ensure uniform thickness and stable performance of each layer, achieving efficient laser energy absorption, ink or dye transfer and protection of the carbon ribbon.

[0047] The present invention has the following beneficial effects:

[0048] 1. In terms of transfer efficiency, the present invention optimizes the material and structure of the light-to-heat conversion layer so that it can absorb laser energy more efficiently and transfer it to the ink or dye layer. Compared with the existing technology, the transfer efficiency is improved by 30%-50%, which can meet the needs of high-speed printing;

[0049] 2. In terms of pattern quality, high definition is due to the fine ink or dye formula, uniform coating process and precise control of laser energy by the protective layer, making the line edges clearer, the pattern details richer, and the clarity 20%-30% higher than the existing technology; high color saturation comes from the selection of high-quality dyes or pigments, the rational use of additives and the good synergy between the layers, the color performance is more vivid and realistic, and the color saturation is 15%-25% higher than the existing technology;

[0050] 3. In terms of substrate adaptability, the release layer composed of various materials and the optimized ink or dye formula enhance the adhesion of the carbon ribbon to substrates of different materials. It shows good adhesion and friction resistance on substrates such as paper, plastic, and leather, greatly broadening the application range of the carbon ribbon. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Figure 1 It is a structural schematic diagram of the high-performance carbon ribbon for laser thermal transfer provided by the present invention.

[0052] Figure 2 This is another schematic diagram of the structure of the high-performance carbon ribbon for laser thermal transfer provided by the present invention.

[0053] Figure 3 This is a printing effect diagram of the high-performance carbon ribbon for laser thermal transfer of Example 1 on coated paper.

[0054] Attached Figure 1 , 2 The structures represented by the labels are listed below:

[0055] 1. Substrate; 2. Release layer; 3. Photothermal conversion layer; 4. Ink layer; 5. Thermal sublimation dye layer. DETAILED DESCRIPTION

[0056] The principles and features of the present invention are described below. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.

[0057] Unless otherwise specified, the test methods used in the examples are conventional methods; the materials, reagents, etc. used are commercially available reagents and materials unless otherwise specified; unless otherwise specified, the parts in the following formulas are parts by mass.

[0058] In a specific embodiment, Figure 1 As shown, the high-performance carbon ribbon for laser thermal transfer includes an ink layer 4, a light-to-heat conversion layer 3, a release layer 2 and a substrate 1 which are arranged in sequence.

[0059] In another specific embodiment, Figure 2As shown, the high-performance carbon ribbon for laser thermal transfer includes a thermal sublimation dye layer 5, a light-to-heat conversion layer 3 and a substrate 1 which are arranged in sequence.

[0060] Embodiment 1:

[0061] Thermal sublimation dye layer ribbon

[0062] PET substrate: Use 4.5μm PET film and corona treat it until the surface dyne value is greater than 48.

[0063] Light-to-heat conversion layer

[0064] 10 parts of carbon nanotubes, 5 parts of graphene, 1 part of polyvinyl pyrrolidone dispersant, 50 parts of N-methyl pyrrolidone, 500 parts of pure water, ultrasonic dispersion for 50 minutes, 84 parts of acrylic resin binder (an optional brand model is Joncryl682, BASF, Germany) are added, and stirred for 75 minutes to obtain a coating. The coating is coated by a gravure coater at a speed of 150m / min, a baking temperature of 90°C, and a thickness of 0.5μm.

[0065] Sublimation dye layer

[0066] Azo dyes (optional brands include CI Disperse Yellow 3, Disperse Red 153, Disperse Blue 3) 10 parts, hindered phenol antioxidant (optional antioxidant 2246) 0.3 parts, polyvinyl butyral resin (optional brand is Sekisui Chemical KS-10) 10 parts, dissolved in 80 parts of a mixed solvent of butanone and toluene (1:1), stirred evenly and coated with gravure, speed 150m / min, baking temperature 90°C. Cyan thickness 1.0μm, magenta 0.8μm, yellow 0.6μm.

[0067] The light-to-heat conversion layer was tested and the light absorption rate of the test coating was > 99%.

[0068] Embodiment 2:

[0069] Ink layer ribbon

[0070] PET substrate: same as in Example 1.

[0071] Light-to-heat conversion layer: the same as in Example 1.

[0072] Ink layer

[0073] 35 parts of thermoplastic polyurethane resin (an optional brand model is R6835), 20 parts of carbon black pigment, 15 parts of polyethylene wax, 15 parts of butanone, 10 parts of toluene, 0.9 parts of high molecular polymer dispersant (an optional brand model is Euka dispersant 560S), 1.2 parts of silicone leveling agent (an optional brand model is BYK-377), after mixing, apply with a scraper at a speed of 150m / min, dry at 80°C, and have a thickness of 2μm.

[0074] Release layer:

[0075] 7 parts of polytetrafluoroethylene powder, 4 parts of silica nanoparticles, 89 parts of polyester resin (an optional brand model is Toyobo VYLON BX-7000A), dissolved in a mixed solvent of toluene and butanone (1.5:1), stirred at high speed for 45 minutes to make a coating. Coating by micro-gravure coater, speed 150m / min, drying at 80℃, thickness 0.5μm.

[0076] Embodiment 3:

[0077] Referring to Example 1, the difference is that 10 parts of carbon nanotubes and 5 parts of graphene can be adjusted to 5 parts of carbon black, 5 parts of carbon nanotubes, and 5 parts of graphene, and still has good light absorption efficiency.

[0078] Performance Testing

[0079] 1. Test equipment and method for transfer efficiency test: Use a high-precision timer to record the time required for the carbon ribbon to transfer a specific pattern (such as a 10cm×10cm all-black pattern) on standard paper at a fixed laser (CryLaS266nm continuous wave laser) power (such as 8W) and pulse frequency (such as 20kHz). The transfer efficiency is expressed in terms of the area (cm2) transferred per unit time. 2 Sample quantity and statistical analysis: Each embodiment and comparative example was tested 5 times, and the average value was taken as the final result. The standard deviation was calculated to evaluate the dispersion degree of the data.

[0080] 2. Pattern quality test Clarity assessment test equipment and methods: Use a high-resolution optical microscope (magnification 500-1000 times) to observe the line edges of the transferred pattern and measure the line width deviation. At the same time, use image analysis software (such as ImageJ) to calculate the pattern clarity parameters, such as edge gradient value. Quantitative standard: Line width deviation within ±5%, edge gradient value greater than 50 is considered good clarity.

[0081] Maximum optical density value evaluation test equipment and method: Use a colorimeter to measure the maximum optical density value that the sublimation ribbon can transfer. Quantitative standard: greater than 2.0 is A grade, greater than 1.8 and less than or equal to 2.0 is B grade, greater than 1.5 and less than or equal to 1.8 is C grade, and less than or equal to 1.5 is D grade.

[0082] 3. Substrate adaptability test

[0083] Test of substrates of different materials: select substrates of various materials such as paper (coated paper is used uniformly), plastic film (such as PET film, PP film, PET film is used uniformly in the test), leather (cowhide leather is used uniformly in the test), etc., and use the same laser thermal transfer parameters for transfer test.

[0084] Adhesion test method

[0085] Tape peeling test: After transfer, stick standard tape (such as 3M tape) on the pattern surface, roll it with a 2kg roller 3 times, then quickly peel off the tape in a 90° direction, observe the pattern peeling, and calculate the percentage of the peeling area. A peeling area of ​​less than 5% is considered to be good adhesion.

[0086] Friction resistance test: Fix the transferred substrate on a friction tester, use a rubber friction head, apply 5N pressure, rub back and forth 100 times at a speed of 100mm / s, observe the pattern wear, and rate it according to the degree of wear (such as 1-5, 5 is no wear, 1 is severe wear).

[0087] Comparative example:

[0088] Comparative Example 1: Referring to Example 1, the difference is that no light-to-heat conversion layer is provided, and the thermal sublimation dye layer (as the primer layer) uses polyvinyl pyrrolidone as the solvent.

[0089] Comparative Example 2: Refer to Example 2, except that no light-to-heat conversion layer is provided.

[0090] Comparative Example 3: Refer to Example 1, except that the material of the light-to-heat conversion layer is carbon black + resin.

[0091] The test results are as follows:

[0092]

[0093] The printing effect of the high-performance carbon ribbon for laser thermal transfer in Example 1 on coated paper is as follows: Figure 3 As shown in the figure, the image has the same effect as traditional thermal sublimation contact printing in both highlight and dark areas, breaking through the limitation that traditional thermal sublimation ribbons cannot be directly printed on weakly coated or uncoated paper such as coated paper.

[0094] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A high-performance carbon ribbon for laser thermal transfer, characterized in that: It includes an ink layer, a light-to-heat conversion layer, a release layer and a substrate which are arranged in sequence; Alternatively, it comprises a thermal sublimation dye layer, a light-to-heat conversion layer and a substrate which are arranged in sequence.

2. The high-performance carbon ribbon for laser thermal transfer according to claim 1, characterized in that: The light-to-heat conversion layer comprises the following components in mass percentage: 8%-15% carbon nanotubes, 3%-8% graphene, and 77%-89% acrylic resin binder; And / or, the light-to-heat conversion layer has a thickness of 0.3-0.8 μm.

3. The high-performance carbon ribbon for laser thermal transfer according to claim 1, characterized in that: The demoulding layer comprises the following components in mass percentage: 5%-10% polytetrafluoroethylene powder, 3%-6% silicon dioxide nanoparticles, and 84%-92% polyester resin; And / or, the release layer has a thickness of 0.1-0.3 μm.

4. The high-performance carbon ribbon for laser thermal transfer according to claim 1, characterized in that: The substrate is a transparent polyethylene terephthalate film, a polypropylene film, a polyethylene naphthalate film, a polyethylene film, a polyvinyl alcohol film or a polymethyl methacrylate film; The thickness of the substrate is 6-12 μm.

5. The high-performance carbon ribbon for laser thermal transfer according to claim 1, characterized in that: The thermal sublimation dye layer comprises a thermal sublimation dye with a sublimation temperature of 100-200° C. and a resin binder, wherein the weight ratio of the resin binder to the thermal sublimation dye is (1:1)-(1:2); and the thickness of the thermal sublimation dye layer is 0.5-1.5 μm.

6. The high-performance carbon ribbon for laser thermal transfer according to claim 5, characterized in that: The thermal sublimation dye is an azo dye or an anthraquinone dye; The thermal sublimation dye is selected from any one of cellulose, polyurethane resin or polyvinyl butyral resin; The thermal sublimation dye layer also contains 1% to 3% by mass of an antioxidant.

7. The high-performance carbon ribbon for laser thermal transfer according to claim 1, characterized in that: The ink layer is prepared from an ink coating liquid: The ink coating liquid comprises the following components in percentage by mass: 30%-45% thermoplastic polyurethane resin, 15%-25% pigment, 10%-20% wax additive, and 20%-30% organic solvent; Alternatively, the ink coating liquid comprises the following components in percentage by mass: 30%-45% of thermoplastic polyurethane resin, 15%-25% of pigment, 10%-20% of wax additive, 20%-30% of organic solvent, and 3%-6% of dispersant; The thickness of the ink layer is 0.5-3 μm.

8. A method for preparing a high-performance carbon ribbon for laser thermal transfer according to any one of claims 1 to 7, characterized in that: The following steps are involved: preparing a substrate, a release layer, a light-to-heat conversion layer and an ink layer in sequence; Alternatively, the substrate, the light-to-heat conversion layer and the thermal sublimation dye layer are prepared in sequence.

9. An application of the high-performance carbon ribbon for laser thermal transfer according to any one of claims 1 to 7, characterized in that: As a sublimation ribbon or full transfer ribbon.

10. The use according to claim 9, characterized in that: Ultraviolet light, visible light or infrared light is used as the laser source.

Citation Information

Patent Citations

  • Thermal transfer film and method of manufacturing OLED display

    CN103158386A

  • Thermal transfer film

    CN103189211A

  • LITI donor film

    CN103620810A

  • Photothermally-induced shape memory composite and preparation method thereof

    CN105153864A

  • Laser donor membrane, preparation method thereof and method for transferring graphene membrane by utilizing laser donor membrane

    CN106744865A